(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The use of radioprotectors is important as one way to decrease radiationrelated deleterious effects on normal tissues. The aim of this research was to study the radioprotective abilities of the newly synthesized compounds such as Cu(II) complexes with tryptophan, histidine and phenylalanine. The rats were exposed to X-ray at 5 Gy dose (LD50/30) after preliminary administration of 10 mg/kg compounds. At 3, 7, 14 and 28 days following irradiation DNA was isolated from rats’ livers. In order to detect defects in the DNA structure on the specified days, the DNA melting parameters were determined, including the melting point, temperature interval of melting and hypochromic effect. The results showed that the Cu(II) complexes derived from tryptophan, histidine and phenylalanine exhibit radioprotective properties. The investigated compounds demonstrated positive effects on the melting parameters of liver DNA, testifying a preservation of the DNA secondary structure stability.